Thermal and mechanical characteristics of local firewood species and resulting charcoal produced by slow pyrolysis - Lubwama, Michael; Yiga, Vianney Andrew; Ssempijja, Ivan; Nalubega Lubwama, Harriet (Biomass Conversion and Biorefinery, 2021)
The main source of fuel for domestic cooking applications in Sub-Saharan Africa is either locally available firewood species or charcoal produced by slow pyrolysis of these species. However, very few studies exist that characterize and quantify physical properties, burning rates, peak temperatures, and calorific values of typical firewood species and resulting charcoal fuels produced by slow pyrolysis. This study evaluated the mechanical and thermal properties of firewood and charcoal from five tree species namely: Dichrostachys cinerea, Morus Lactea, Piliostigma thonningii, Combretum molle, and Albizia grandibracteata. Characterization was done by scanning electron microscopy, thermogravimetric analysis, bomb calorimetry, Fourier transform infrared spectroscopy, bulk density measurements, and durability, water boiling and absorption tests. SEM images showed the development of macropores on charcoal after slow pyrolysis. Peak temperatures during firewood and charcoal combustion ranged between 515.5–621.8 °C and 741.6–785.9 °C, respectively. Maximum flame temperatures ranged between 786.9–870.8 °C for firewood and 634.4–737.3 °C for charcoal. Bulk densities and calorific values of charcoal species were higher than those for firewood species. Drop strengths for firewood were all 100% while for charcoal were between 93.7 and 100%. Water boiling tests indicated that firewood fuel performed better that charcoal fuel for low amounts of water due to higher maximum flame temperatures obtained during combustion of firewood.
Keywords: Charcoal; Firewood; Maximum Flame Temperature; Peak Temperatures; Pyrolysis; Thermogravimetric analysis